Implementasi Program Rumah Tidak Layak Huni (RTLH) di Kota Tangerang Selatan - Reza Chandra Tirtana; Yudan Rasyid; Fadhli Hibatullah (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
Development is a change that leads to improvement which aims to live a decent and prosperous life in a country. These social problems arise in the community because the need for livable housing is not immediately addressed so that the uninhabitable housing program is a development priority proclaimed by the South Tangerang city government to date. The purpose of this study was to determine the implementation of the uninhabitable housing program (RTLH) in South Tangerang City. This research uses a qualitative descriptive method. The results of this study show that the implementation of the program has been realized well enough to help the less fortunate in obtaining a decent living, especially for a comfortable and safe place to live. From the implementation of the policy, which statistically shows that the policy from 2020 to 2021 has succeeded in providing house renovation assistance to 403 uninhabitable housing units, the evidence for the overall target can already be seen. Although there are some that are uneven so that the overall target has not been reached.